2013
DOI: 10.3892/ijmm.2013.1402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced oxidation protein products on the proliferation and osteogenic differentiation of rat mesenchymal stem cells

Abstract: Abstract. Advanced oxidation protein products (AOPPs) as a novel marker of oxidative stress, are involved in a variety of diseases, including osteoporosis. Although a number of studies have shown the possible functions of AOPPs in biological processes, little is known about the role of AOPPs in the pathogenesis of osteoporosis. In this study, we aimed to investigate the effect of AOPPs on the proliferation and osteogenic differentiation of rat mesenchymal stem cells (MSCs). MSCs, isolated from bone marrow, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In general, undifferentiated MSCs have fewer mitochondria than differentiated MSCs, though the mitochondrial copy number, OXPHOS supercomplex, SOD expression, mitochondrial biogenesis and ROS levels are all significantly increased after specific differentiation . ROS imbalance will lead to a significantly reduced MSC differentiation capacity, thus limiting MSC applications in vitro and in vivo. When adult MSCs are incubated under stress‐inducing conditions, they are considered to be in a state of cyclic stretch and produce more ROS and have weaker differentiation capacities .…”
Section: Ros Generation and The In Vitro Differentiation Fate Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, undifferentiated MSCs have fewer mitochondria than differentiated MSCs, though the mitochondrial copy number, OXPHOS supercomplex, SOD expression, mitochondrial biogenesis and ROS levels are all significantly increased after specific differentiation . ROS imbalance will lead to a significantly reduced MSC differentiation capacity, thus limiting MSC applications in vitro and in vivo. When adult MSCs are incubated under stress‐inducing conditions, they are considered to be in a state of cyclic stretch and produce more ROS and have weaker differentiation capacities .…”
Section: Ros Generation and The In Vitro Differentiation Fate Of Mscsmentioning
confidence: 99%
“…In general, undifferentiated MSCs have fewer mitochondria than differentiated MSCs, though the mitochondrial copy number, OXPHOS supercomplex, SOD expression, mitochondrial biogenesis and ROS levels are all significantly increased after specific differentiation. 51,52 ROS imbalance will lead to a significantly reduced MSC differentiation capacity, 53 thus limiting MSC applications in vitro and in vivo.…”
Section: Diffe Rentiation Fate Of Mscsmentioning
confidence: 99%
“…However unregulated levels of ROS are harmful, which lead to the induction of apoptosis (Martindale and Holbrook, 2002). Some reports suggested that ROS may be involved in the proliferation of osteoprogenitors and their subsequent differentiation (Imhoff and Hansen, 2011;Sun et al, 2013). The ROS level is increased after fracture, and oxidative stress may be proportional to the number of bones fractured (Turgut et al, 1999;Prasad et al, 2003).…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Previous studies have demonstrated that AOPPs may inhibit the proliferation and differentiation of rat osteoblastic cells and rat mesenchymal stem cells (8,9). As the most abundant cell type in bone (90–95%), osteocytes function as more than just mechanosensors in bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%